Negotiating Diversity Identity, Pluralism and Democracy - Sauca, José-Maria; Gagnon, Alain-G (Diversitas, 2014)
This book provides new insights into the negotiation and management of diversity in complex democratic settings. Much debate has been generated recently over questions of human rights and dignity with the aim of empowering and improving the recognition of smaller nations. The book's central idea is that respect for democracy and protection of human rights represent the most potent ways for the advancement and enrichment of cultural, ideological and legal pluralism. The pursuit and accomplishment of such objectives can only be achieved through negotiation that leads to the accommodation and empowerment of minority groups and nations. Negotiating Diversity brings into dialogue political scientists, philosophers and jurists, and enriches a major discussion launched some years back by Yael Tamir's Liberal Nationalism, Alain-G. Gagnon and James Tully's Multinational Democracies, as well as Wayne Norman's Negotiating Nationalism, and Will Kymlicka's Multicultural Citizenship.